Dilution and clustering of Fe in the rutile phases of TiO2 and SnO2 (2008)
ABSTRACT: Dilute magnetic semiconductors of Fe-doped SnO2 and TiO2 with the structure of rutile were prepared in forms of powder and thin films using the techniques of sol gel and pulsed-laser deposition. We present the results of measurement of vibrational density of states of Fe impurity dopants in these oxides and demonstrate the cases of dilution and clustering. The oxygen pressure during the film deposition was varied between 10−1 and 10−8 Torr. In TiO2 films made at 10−1 Torr, Fe is diluted, however, in films made at 10−8 Torr Fe is clustered. The case of true Fe dilution in SnO2 is also shown. In spite of larger mass defect for Fe in SnO2 than that for Fe in TiO2 the dilute Fe species probe the phonon states in SnO2 more faithfully than in TiO2. This result is understood in terms of the combined effect of mass defect and nearest-neighbor force-constant changes. The impurity modes are more pronounced in TiO2 than in SnO2 due to ca. 10% difference of the lattice cell volumes between these two rutile oxides.